Reliability and discriminative ability of a new method for soccer kicking evaluation - Radman, I.; Wessner, B.; Bachl, N.; Ruzic, L.; Hackl, M.; Baca, A.; Markovic, G. (PLOS ONE, 2016)
The study aimed to evaluate the test-retest reliability of a newly developed 356 Soccer Shooting Test (356-SST), and the discriminative ability of this test with respect to the soccer players' proficiency level and leg dominance. Sixty-six male soccer players, divided into three groups based on their proficiency level (amateur, n = 24; novice semi-professional, n = 18; and experienced semi-professional players, n = 24), performed 10 kicks following a two-step run up. Forty-eight of them repeated the test on a separate day. The following shooting variables were derived: ball velocity (BV; measured via radar gun), shooting accuracy (SA; average distance from the ball-entry point to the goal centre), and shooting quality (SQ; shooting accuracy divided by the time elapsed from hitting the ball to the point of entry). No systematic bias was evident in the selected shooting variables (SA: 1.98±0.65 vs. 2.00±0.63 m; BV: 24.6±2.3 vs. 24.5±1.9 m s-1; SQ: 2.92±1.0 vs. 2.93±1.0 m s-1; all p>0.05). The intra-class correlation coefficients were high (ICC = 0.70-0.88), and the coefficients of variation were low (CV = 5.3-5.4%). Finally, all three 356-SST variables identify, with adequate sensitivity, differences in soccer shooting ability with respect to the players' proficiency and leg dominance. The results suggest that the 356-SST is a reliable and sensitive test of specific shooting ability in men`s soccer. Future studies should test the validity of these findings in a fatigued state, as well as in other populations.